Is a Ketogenic Diet Superior to a High-Fat, High-Cholesterol Diet Regarding Testicular Function and Spermatogenesis? - Liu, Chin-Yu; Chang, Ting-Chia; Lin, Shyh-Hsiang; Tsao, Chih-Wei (Frontiers in Nutrition, 2022)
The aim of this study was to investigate the effects of a ketogenic diet on metabolic dysfunction, testicular antioxidant capacity, apoptosis, inflammation, and spermatogenesis in male mice with high-fat and high-cholesterol diet-induced obesity. Forty-two male C57BL/6 mice were fed either a normal diet (NC group) or a high-fat and high-cholesterol (HFC) diet (HFC group) for 16 weeks, and mice randomly chosen from the HFC group were later divided into two groups: the first were maintained on the original HFC diet, and the second were fed a medium-chain triacylglycerol (MCT)-based ketogenic diet for 8 weeks (KD group). A poor semen quality was observed in the HFC group, but this was eliminated by the ketogenic diet. Both the HFC and KD groups exhibited enhanced apoptosis protein expressions in testis tissue, including caspase 3 and cleaved PARP, and higher inflammation protein expressions, including TNF-α and NF-κB. However, the KD group exhibited a statistically-significant reduction in lipid peroxidation and an increased glutathione peroxidase level as compared with the HFC group. The HFC diet induced obesity in mice, which developed body weight gain, abnormal relative organ weights, metabolic dysfunction, and liver injury. Overall, the results showed that a ketogenic diet attenuated oxidative stress and improved the semen quality reduced by the HFC diet.